Incivility on Facebook during 8M: comments on posts by five Spanish-language media outlets - Robles Olivos, Rafael Alexis; Jácobo Morales, Daniel; García Wong Kit, Javier Ernesto (Estudios sobre el Mensaje Periodístico, 2026)
The present study analyzes the incivility present in Facebook user comments made on the posts of five Spanish-speaking media outlets with the highest digital reputation – El País (Spain), El Mundo (Spain), El Comercio (Peru), ABC (Spain), and La Nación (Argentina) – during the coverage of International Women’s Day (8M) between 2021 and 2025. Based on a mixed content analysis applied to 550 comments/responses selected by volume of interaction (110 textual contents for each medium), the research classifies the levels and types of uncivil behavior according to typologies by Rosenberg (2018) and Bentivegna and Rega (2024). The results obtained show that verbal hostility is widespread across all studied media outlets, with a predominance of high and moderate incivility, characterized by vulgar language, identity-based name-calling/disqualification, sarcasm, and mutual reinforcement among users. Likewise, aggressive interaction was manifested towards both figures mentioned in the news and other users, with discriminatory expressions frequently directed at women, sexual minorities, or ideological groups. The study, therefore, confirms patterns described in previous literature, including the defensive effect, polarization, the impunity fostered by anonymity, and the degradation of debate in contexts of political discussion. Finally, the need to extend the analysis to other platforms and explore the role of non-textual interactions in the construction of the digital deliberative climate is raised